The psychometric properties of the Test for Creative Thinking (TCT-DP) in a sample of 8–10-year-old Lithuanian children - Girdzijauskienė, Sigita; Nasvytienė, Dalia; Butkienė, Dovilė; Gintilienė, Gražina; Dragūnevičius, Kęstutis (Psichologija, 2018)
This article analyzes whether the Drawing Test for Creative Thinking (TCT-DP) can be applied as a reliable and valid instrument for the assessment of the creative potential of 8–10-year-old Lithuanian children. Currently in Lithuania, there is no such test for this particular age. Empirical and theoretical research shows that the developmental pace and structure of creative potential among children of primary school age may be specific (Urban, 1991; Rudowicz, 2004; Lubart et al., 2010; Ju et al., 2015; Jastrzębska & Limont, 2017; Welter et al., 2017). The study consisted of 497 primary pupils across grades 2–4. The quota sample was based on the criteria of a child’s age, gender, and school location. All children are assessed by A and B forms of TCT-DP; the Wechsler’s Intelligence Scale for Children (WISC-IIILT) was administered to 63 randomly selected children for the purpose of verifying discriminant validity. The SPSS Statistics 25 software package was used for data analysis. The results revealed a significant difference in the creative potential among children of age 8 and age 10; the results for girls and boys were similar. The evaluation of several types of reliability had shown good or excellent inter-rater reliability, the accuracy of the categories rating system, minimally sufficient stability of the aggregate score of A and B forms, and an inadequate internal consistency of these forms. Both A and B forms equally well differentiated the level of children’s creativity. The TCT-DP construct validitywas confirmed by the stable increase of performance of 8-year-olds, 9-year-olds and 10-year-olds. Exploratory factor analysis has highlighted that the creative potential of children aged 8–10 years is best described by three factors – Originality, Adaptability and Risk taking. That generally consists with the findings of other researchers (Rudowicz, 2004; Lubart et al., 2010) that emphasize originality, nonconventionalityon the one hand, and adaptation to the requirements on the other hand. However, it is difficult to consistently match these results with the original data on TCT-DP, as Urban and Jellen (1995) performed a factor analysis in a joint sample of 4–16-year-old children. Low correlations with the WISC-IIILT results confirm the discriminant validity of TCT-DP.
Keywords: assessment of children’s creativity; TCT-DP; TCT-DP reliability; TCT-DP validity